ANALYSIS OF LINEAR ACCELERATOR (LINAC) AS CANCER TREATMENT IN KEN SARAS HOSPITAL, SEMARANG - Muslimah Putri Utami; Gatot Murti Wibowo; Mohamad Hidayatullah (Journal of Applied Health Management and Technology, 2021)
Background: Based on riskesdas data in 2013, the prevalence of cancer in Indonesia reached 1.4% or around 347,792 people. The technique used at Kensaras Hospital for the use of Electalinac for IMRT engineering and Linac Siemens for 3D engineering with energies of 5 mV, 7 mV, 8 mV, 10 mV, 12 mV, 14 mV. Radiotherapy simulation using the GE 16 slice CT Simulator with adequate space, thermoplast masks, individual blocks and universal blocks, and bolus. Constraints that occur in the use of blocks for Siemens linac which still use manual blocks do not use MLC.Methods: Research analysis using SRL PICO method seeks clinical information in scientific evidence-based health science practices. The results of literature search show that the goal of radiotherapy is to provide the maximum radiation needed to kill cancer, while the minimum to the surrounding healthy tissue.Results: The static MLC method is a method in which the MLC moves to form a segment when the radiation stops and MLC stops as long as the radiation lasts for each gantry angle and MLC stops for radiation and so on for each gantry angle. Meanwhile, the kensaras hospital for Linac Siemens still uses a manual block made from a chimney and is attached to the linacgantry which is prone to falling and having to replace the block every corner. Conclusion: Radiation therapy with a linear electron accelerator is experiencing rapid development and is a cancer therapy that is relatively inexpensive and does not provide radioactive waste. The use of MLC is safer and can move to form segments when radiation stops and MLC stops during radiation for each angle of the gantry.